Mechanism of Zn salt-induced deactivation of a Cu/activated carbon catalyst for low-temperature denitration via CO-SCR. Issue 24 (19th May 2022) - Wen, Zhenjing; Huang, Bangfu; Shi, Zhe; Yang, Zhengyu; Dai, Meng; Li, Wanjun; Zi, Gaoyong; Luo, Liubin
Abstract : Zn slats compete with CO and NO for the active sites. Cl − not only occupies oxygen vacancies but also inhibits the Oβ migration. SO4 2− increases the surface acidity and promotes the Oβ supplementation, which inhibits toxicity. Abstract : In the process of industrial flue gas denitration, the presence of heavy metals, especially Zn salts, is known to lead to the deactivation of the denitration catalysts. However, the specific mechanism of the catalyst deactivation remains unclear. In this paper, the mechanism of the ZnCl2 - and ZnSO4 -induced deactivation of low-temperature denitration catalysts in the carbon oxide (CO) selective catalytic reduction (CO-SCR) reaction was investigated using a Cu/activated carbon (AC) catalyst, in which HNO3 /AC was used as the carrier. Cu/AC, ZnCl2 –Cu/AC, and ZnSO4 –Cu/AC catalysts were prepared by the incipient wetness impregnation method. The physicochemical properties of the catalyst were examined via the Brunauer–Emmett–Teller method, X-ray diffraction, X-ray photoelectron spectroscopy, and Fourier transform infrared spectroscopy analyses, which proved the mechanism of catalyst denitrification and enabled the elucidation of the toxicity mechanism of the Zn salts on the Cu/AC catalyst for CO-SCR denitration at low temperatures. The results show that Zn doping reduces the physical adsorption of CO and NO and decreases the concentration of Cu 2+ and chemisorbed oxygen (Oβ ), leading to the reduction of active sites and oxygen vacancies, thus inhibiting the denitration reaction. Moreover, ZnCl2 is more toxic than ZnSO4 because Cl − not only occupies oxygen vacancies but also inhibits Oβ migration. In contrast, SO4 2− increases the surface acidity and promotes Oβ supplementation. This study can provide a reference for the development of CO-SCR denitration catalysts with high resistance to Zn salt poisoning.